2006
DOI: 10.1002/micr.20237
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of rabbit peripheral nerve repair with end‐to‐side neurorrhaphy in rabbits

Abstract: This study was designed to quantitatively assess long-term end-to-side neurorrhaphy in rabbits. The cut right ulnar nerve was repaired and sutured to the median nerve, in which a perineurial window was created in an end-to-side fashion 3 cm above the elbow joint. Both the extent of the reinnervation and the integrity of the intact donor nerve were evaluated in 36 rabbits randomly treated with fresh or delayed nerve repair. Evaluations included motor nerve conduction velocity (MNCV), dry muscle weight (DMW), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…After these factors are released from Schwann cells by diffusion, they penetrate through the epineurium into the perineurium. In this way, directed collateral sprouting from the region closest to the injury site occurs at the Ranvier nodes of the donor nerve [61].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After these factors are released from Schwann cells by diffusion, they penetrate through the epineurium into the perineurium. In this way, directed collateral sprouting from the region closest to the injury site occurs at the Ranvier nodes of the donor nerve [61].…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells stimulate axonal regeneration from both the distal nerve stump and the nodes of Ranvier of the donor nerve [54,56]. This mechanism is indirectly controlled by neurotropic factors [61]. After these factors are released from Schwann cells by diffusion, they penetrate through the epineurium into the perineurium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, when there is no injury to the donor nerve, nerve regeneration can occur following endto-side anastomosis, but several experimental studies have shown that when the donor nerve had a fenestration, the effect of nerve regeneration was better [71][72][73][74]. Although there are still controversies over whether fenestration can damage the donor nerve, many studies have confirmed that the fenestration of the epineurium can cause a slight damage to the donor nerve, but does not affect the donor nerve function [75][76][77]. this approach does not cost the donor function when nerve grafting.…”
Section: Epineurium or Perineurium Windowmentioning
confidence: 99%